Improvement of Wind Power Utilization Through Flexible Operation of Data Center in Wind Parks - Ahmadi, Mehdi; Knorr, Lukas; Meschede, Henning (Renewable Energy)

Graph Neural Network Surrogates for Uncertainty Quantification in Multi-Node Energy System modeling - Prina, Matteo Giacomo; Knorr, Lukas; Schlosser, Florian; Meschede, Henning; Misconel Schreiber, Steffi; Manepace, Andrea; Sparber, Wolfram

Influence of the Etching Material Deposition Rate and Annealing Time on Nanohole Morphology Etched into InP/In0.52Al0.48As Layers via Local Droplet Epitaxy - Deutsch, Dennis; Reuter, Dirk (Crystals)
Local droplet etching and subsequent refilling enables the fabrication of highly symmetric quantum dots with low fine structure splitting, suitable for generating polarization entangled photons. While well established in GaAs/AlxGa1−xAs, this approach does not yield emission in the telecom bands required for low loss fiber-based quantum communication. To achieve emission at 1.55 μm, local droplet etching must be adapted to alternative material platforms such as InP. Here, we systematically investigate how the etching material deposition rate and etching time influence nanohole morphology in In0.52Al0.48As layers lattice-matched to InP. In the first experiment, InAl was deposited at fluxes of 0.2–4.0 Å s−1 at Tetch = 350 °C and 460 °C. Lower fluxes produced nanoholes with lower density and larger ring diameters, indicating fewer and larger initial droplets, consistent with scaling theory. The average nanohole diameter decreased monotonically with increasing flux, whereas the average depth showed no clear dependence on flux. In the second experiment, etching times of 30–600 s were tested for InAl, In, and Al droplets. Average nanohole diameters remained constant for Al across all etching times, but decreased for In and InAl with increasing etching time, suggesting sidewall redeposition during etching. For all droplet types, depths peaked at intermediate times and decreased for prolonged etching, consistent with material diffusion into the nanohole after droplet consumption.

Das Sieb des Eratosthenes - Hoffmann, Jan Sören; Stoppel, Hans-Jürgen (mathematik lehren)

These I »Deutsch im beruflichen Kontext«. Status quo und Perspektiven - Niederhaus, Constanze; Dvorecky, Michal (Zeitschrift für Deutsch im Kontext von Mehrsprachigkeit)

Corporate Tax Planning and Technology-Based Enforcement - Dyck, Daniel
This study examines how strengthening tax enforcement by increasing human enforcement capacity and improving tax audit technology affect tax audit efficiency. I employ an economic model in which a tax manager’s tax planning effort shapes corporate tax planning and a strategic tax auditor makes a technology-based audit decision. I show that strengthening tax enforcement always increases tax revenues, but decreases the number of audits only under narrow conditions, so that its effect on tax audit efficiency is often ambiguous. Improving tax audit technology has more nuanced implications. When the strength of tax enforcement is sufficiently high, gradual improvements in tax audit technology crowd out audit incentives and, surprisingly, reduce tax revenues, while sufficiently large improvements can overturn this adverse revenue effect. At the same time, improved technology lowers unnecessary audits once the strength of tax enforcement exceeds a minimum level. Therefore, sufficiently large technology improvements improve tax audit efficiency once this minimum level is exceeded. The results have important policy and empirical implications in an environment of constrained fiscal budgets and rapidly advancing audit technologies.

(Re)Polizicizing the Teen Genre: On the (Queer) Utopian Potentials of Netflix's Sex Education - Hartmann, Alexandra (Political Education and American Studies)

Share price reactions to tariff imposition announcements during the first Trump administration - Wengerek, Sascha Tobias; Uhde, André; Hippert, Benjamin (Finance Research Letters)
This study analyzes the impact of tariff imposition announcements on the stock prices of 1,194 U.S. companies during the first Trump administration, using a unique sample of 4,624 announcements made by or against the U.S. between January 2018 and August 2019. We find that tariff announcements lead to negative (cumulative) average abnormal stock returns. These negative wealth effects occur regardless of whether the Trump administration imposes safeguard tariffs to protect domestic industries or foreign countries announce retaliatory tariffs. Moreover, the adverse impact is primarily driven by announcements involving China, with variations linked to sector-specific, tariff, trade, and firm characteristics.
Keywords: Geopolitical risk; Protectionism; Strategic trade policy; Tariffs; Trade conflict; U.S. – China trade war

Influence of different oxide thicknesses on the friction induced and continuous solid-state recycling of aluminum scrap - Gabsa, Steffen; Homberg, Werner; Goller, Timothy; Nordieker, Ansgar Bernhard; Grundmeier, Guido (Materials Research Proceedings)
Abstract. Saving emissions and a circular economy are key aspects of sustainable production and compliance global climate change targets. Friction-induced solid-state recycling of aluminum scrap to production endless semi-finished products. Scrap is fed into a continuously rotating wheel. This requires less energy compared to heat-based recycling processes. Different sizes, shapes and surfaces of chips can be used as starting material in the process. The influence of this has been shown in past publications. A native oxide layer is a fixed component of aluminum surface. This layer is broken up during the forming process, allowing the aluminum to bond. In addition to the geometry, the surface finishes and the thickness of the oxide layer are therefore also important input variables in friction-induced solid-state recycling. The oxide layers on the chips were determined for the investigation. In addition, different layer thicknesses were produced to survey their influence. The resulting semi-finished products were evaluated on the basis of their tensile strength and microstructure. The main result of the investigations is the fact that semi-finished products made from chips with thicker oxide layers tend to be more brittle. In addition, thick oxide layers cause microstructural and surface defects.

Konstruktionistisches Geometrielernen durch epistemisches Programmieren in Scratch - Stoppel, Hans-Jürgen; Hüsing, Sven

Mathematik mit Scratch - Stoppel, Hans-Jürgen; May, Michel (mathemathik lehren)

Entlang der Vielecke - Stoppel, Hans-Jürgen (mathemathik lehren)

Mathematik weiterdenken - Wie informatisches Denken die Mathematik stärkt - Stoppel, Hans-Jürgen; Plangg, Simon; Büscher, Carina (mathemathik lehren)

Neural Reasoning for Robust Instance Retrieval in SHOIQ - Kamdem Teyou, Louis Mozart; Friedrichs, Luke; Kouagou, N'Dah Jean; Demir, Caglar; Mahmood, Yasir; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille

Workarounds—A Domain-Specific Modeling Language - Krabbe, Carolin; Assbrock, Agnes; Reineke, Malte Fabian; Beverungen, Daniel (Proceedings of the 20th International Conference on Wirtschaftsinformatik (WI25))

Zwischen Distanz und Involviertheit. Nähe zum Forschungsfeld in der Situational Analysis im Spannungsfeld von nordamerikanischer und deutschsprachiger Forschungstradition. - Ballweg, Sandra (Zeitschrift für Rekonstruktive Fremdsprachenforschung)

Innovative Computerbasierte Musikinterfaces (ICMI) - Engeln, L.; Pöpel, C.; Reckter, H.; Hadjakos, A.; Berndt, Axel; Trump, S.; Schnell, N.; Akkermann, M.; Jürgens, E. (Mensch und Computer 2025 - Workshopband)

Digitale Orgel, digitales Notenpult - Berndt, Axel (9th Autumn Workshop of Young DEGA)

ChoraleBricks: A Modular Multitrack Dataset for Wind Music Research - Balke, Stefan; Berndt, Axel; Müller, Meinard (Transactions of the International Society for Music Information Retrieval)

Detmold musical Instrument Timbre Explorer (DmITE): Interactive visualization of musical instruments radiation pattern using IEEE 1599 - Mauro, Davide Andrea; Ludovico, L. A.; Aydin, H. H.; Berndt, Axel; Grothe, T. (AM.ICAD: Audio Mostly & ICAD Joint Conf.)